2023
DOI: 10.1590/1678-992x-2021-0283
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic stoichiometry in tropical soil under pure and mixed plantations of eucalyptus with N2-fixing trees

Abstract: Soil enzymes play a fundamental role in nutrient cycling in forest systems. The stoichiometry of C, N, and P-acquiring enzymes has been used to indicate nutrient limitation in the soil. However, the enzymatic stoichiometry remains poorly understood in pure and mixed eucalypt plantations. Thus, this study aims to assess the activity of enzymes in the soil to address the hypothesis that the introduction of N 2 -fixing trees could influence the enzymatic stoichiometry on C, N, and P cycling. The activity of β-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…These results suggest that monoculture patterns induce a shift from nitrogen limitation to phosphorus limitation in microbes, whereas the construction of mixed forests or the application of rotational patterns that introduce other tree species can aid in regulating the nutrient limitation status of microorganisms and reduce the microbial phosphorus demand. This finding confirmed the first hypothesis of present study, and was similar to the observations of Pereira et al (2023) [70] on mixed plantations of Eucalyptus sp. and nitrogen-fixing species.…”
Section: Assessment Of Nutrient Limitation From Soil Es Characteristicssupporting
confidence: 94%
“…These results suggest that monoculture patterns induce a shift from nitrogen limitation to phosphorus limitation in microbes, whereas the construction of mixed forests or the application of rotational patterns that introduce other tree species can aid in regulating the nutrient limitation status of microorganisms and reduce the microbial phosphorus demand. This finding confirmed the first hypothesis of present study, and was similar to the observations of Pereira et al (2023) [70] on mixed plantations of Eucalyptus sp. and nitrogen-fixing species.…”
Section: Assessment Of Nutrient Limitation From Soil Es Characteristicssupporting
confidence: 94%
“…The introduction of legumes into cropping systems (Sekaran et al, 2019), the permanence of plant residues in the soil (Malobane et al, 2020), and the high temperatures found in tropical dry regions are factors that increase urease activity. It is well known that the Nacquiring enzyme is influenced by inputs of plant litter (Mukumbareza et al, 2016) as well as the presence of Nfixing tree species (Pereira et al, 2023). On the other hand, the land uses with Ipê forest (TAB) and tropical forest (TDF) showed the highest values of N-acquiring enzyme at 5−10 cm depth.…”
Section: Discussionmentioning
confidence: 98%
“…One method to estimate the nutrient demands by microbes and C, N, and P availability in soils is the stoichiometry of C-, N-, and P-acquiring enzymes (Sinsabaugh et al, 2009) and it has been applied in several previous studies (Zhang et al, 2021;Araujo et al, 2022;Pereira et al, 2023). In addition, the enzymatic stoichiometry can indicate which conditions C, N, and P are limited to soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The plant residues from Acacia mangium (e.g., detritus, rhizodeposition) have a lower C/N ratio (C/N~34) than eucalyptus (C/N~58), which favors BG activity [16]. It provides evidence of the advantage of E + A systems over the E. grandis monocropping system (E) in providing better SQ scores, since greater BG activity results in faster organic matter decomposition and nutrient releasing for microbial communities in the topsoil [47].…”
Section: Discussionmentioning
confidence: 99%
“…Acid phosphatase plays an important function in P mineralization since it hydrolyses organic P compounds into phosphomonoesters and mineralizes these compounds into orthophosphate, boosting P dynamics in the soil [54]. Thus, in addition to C-cycles enzymes (i.e., β-glucosidase), the P-acquiring enzyme can also indicate important changes in SQ under mixed forest plantations between eucalypts and acacia [47,55].…”
Section: Discussionmentioning
confidence: 99%